The Effect of Service Quality, Brand Image, and Customer Perceived Value on Customer Satisfaction Kopi Kenangan (Study On Gen Z Consumers Of Kopi Kenangan In Surabaya) - Dilan Serviako Sinaga; R. Yuniardi Rusdianto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The growth rate of modern coffee shops in Indonesia is accelerating, in line with the changing lifestyles of urban communities, especially Generation Z, who are familiar with hanging out, flexible working, and experience-based consumption. In an increasingly competitive environment, it is not enough for companies to simply sell delicious products; Customer Satisfaction must be built and maintained consistently. This is where Kopi Kenangan, as one of the local coffee brands with a large network, is required to continuously pay attention to Service Quality at its outlets, the Brand Image that sticks in consumers' minds, and the value that is truly felt from each purchase. This study stems from these needs and aims to examine the influence of Service Quality, Brand Image, and Customer Perceived Value on Customer Satisfaction among Generation Z consumers of Kopi Kenangan in the city of Surabaya. The approach used is quantitative with an associative descriptive research type. Data was obtained through a questionnaire survey of 160 respondents who had purchased Kopi Kenangan and resided in Surabaya, then analyzed using multiple linear regression. The results of the analysis show that the three independent variables simultaneously affect Customer Satisfaction. When tested partially, Service Quality, Brand Image, and Customer Perceived Value were also proven to have a positive and significant influence. These findings indicate that good service experience, strong Brand Image, and perceived value commensurate with the price and quality of the product play an important role in shaping the satisfaction of Generation Z Kopi Kenangan consumers. Keywords: Service Quality, Brand Image, Customer Perceived Value, Customer Satisfaction.